Salespersons' empathy as a missing link in the customer orientation–loyalty chain: an investigation of drivers and age differences as a contingency. Issue 3 (2nd July 2016) - Gerlach, Gisela I.; Rödiger, Kai; Stock, Ruth Maria; Zacharias, Nicolas A.
Abstract : Salespersons' customer orientation has attracted considerable attention from practitioners and researchers. By distinguishing customer-oriented attitude from behavior, this study sheds light on customers' perceptions of salespersons' empathy, as a missing link between customer orientation and customer-related outcomes. Noting the increasing age diversity among salespersons and customers, this study also investigates whether age differences in salesperson–customer dyads moderate the relationships of salespersons' customer-oriented attitude and behavior with customer outcomes. Finally, this study examines salespersons' climate perceptions as antecedents of their customer-oriented attitudes. Results of multilevel modeling with data from 164 salespersons and 405 customers reveal that salesperson empathy, as perceived by customers, is an important facilitator of the customer orientation–satisfaction relationship. When there are large age differences, salespersons' customer-oriented attitude becomes more important for making customers feel understood by salespersons. Regarding antecedents, salespersons' customer-oriented attitude is influenced by their perceptions of team-member exchange and age-inclusive climate.